Three-Dimensional Digital Surgical Planning and Rapid Prototyped Surgical Guides in Bernese Periacetabular Osteotomy - Bruno Gonçalves Schröder e Souza; Flavia de Souza Bastos; Valdeci Manoel de Oliveira; Alfredo Chaoubah (Case Reports in Orthopedics)
Bernese periacetabular osteotomy (PAO) developed by Ganz is currently the treatment of choice for skeletally mature symptomatic patients with developmental dysplasia of the hip (DDH) without osteoarthritis. However, the steep learning curve and considerable number of severe complications lead surgeons to seek for alternatives to promote greater reproducibility and safety of this procedure. This is a report of a DDH case surgically treated with the aid of a digital three-dimensional (3D) planning and rapidly prototyped sterile ABS plastic osteotomy guide, developed in Brazil. We present details regarding the planning, guide production, and surgical technique and report the early results of this treatment approach in a single patient. Digital 3D planning and rapidly prototyped surgical guides are applicable and helpful in PAO surgery as shown in this case. We noted no safety issues, good accuracy, and low production costs with this approach.